What drives private equity performance in emerging markets? An African perspective - Cata, Olwethu (Department of Finance and Tax, 2025)
Despite the increasing amounts of capital being dedicated to the asset class, few attempts have been made to evaluate Private Equity (PE) returns in emerging markets and for Africa specifically. Understanding the risk factors associated with PE returns in emerging markets and whether institutional investors can expect adequate compensation for accepting such risks is important to optimal asset allocation. This thesisinvestigates PE performance using a novel dataset of 250 portfolio investments made and exited by 28 General Partners (GPs) across 52 funds in Africa over the period 1996 to 2019. It addresses the following four research questions: (1) How has PE in Africa performed relative to public markets? (2) Is the performance achieved by GPs on the continent persistent? (3) What determines the holding periods of PE investments on the continent? (4) How do macroeconomic conditions impact PE returns on the continent? In doing so, the study makes a significant original contribution to the literature on PE performance by providing new evidence from a minimally investigated region and contributes insights that have practical significance for the capital allocation strategies of institutional investors allocating to PE funds on the continent. The contributions are made in four sequential studies. The first examines how PE in Africa has performed relative to public markets. To do this, public market equivalent returns were calculated, which represent the return that an investor would have received if an equivalent investment had been made in the MSCI Emerging Market Index. The findings indicate that, on a gross of fees basis, a dollar invested in private equity in Africa has, on average (median), returned 78% (37%) more than a dollar invested in the MSCI Emerging Market Index over the period 1996 to 2019. Not only have top quartile funds outperformed the index, but so have the average, median, and bottom quartile funds - implying better relative performance than has previously been reported for PE in emerging markets. These results explain the recent increases in investor allocations to PE investments in Africa and imply that an allocation to PE may contribute positively to an allocator's overall portfolio return. The second study investigates whether the GP performance in Africa is persistent using the deal level approach introduced by Braun et al. (2017) that allows for a decomposition of the sources of persistence. The findings suggest that IRR performance is persistent across subsequent deals exited by the same GP and indicate that persistence is driven by the third and top quartiles. This implies conventional wisdom to back GPs that have previously achieved top quartile performance holds in Africa. In exploring the sources of persistence, this study finds that GPs differ systematically in their ability to achieve timeous and high value exits and that this factor has a substantial influence on persistence. Unlike the developed markets literature that documents the disappearance of persistence, the results indicate that the increasing capital flows to the PE industry on the continent have had a limited negative influence on persistence. This suggest that past PE performance in Africa is a good predictor of future returns. The third study investigates the factors that have an impact on PE investment holding periods in Africa. It focuses on the impact of deal characteristics and market conditions on holding periods and uses survival analysis to examine how these factors impact exit behavior. The results indicate that investment duration is persistent across subsequent deals exited by the same GP. This suggests that the ability to timeously realise value is attributable to skill and implies that investment duration may be an important dimension of GP selection. Furthermore, contrary to the increasing holding periods documented by studies focused on developed PE markets, the resultsindicate that the holding periods of PE dealsin Africa have declined over time in line with an improving exit environment as more capital is dedicated to the asset class on the continent. The results also indicate that holding periods are countercyclical and so are lower for investments held when the economy is performing, credit spreads are low, and aggregate industry commitments are increasing. This suggests that GPs on the continent time their exits to take advantage of favourable market conditions. The fourth study uses quantile regression to investigate the impact of macroeconomic conditions on PE returns and examines the combined impact of deal, GP, and macroeconomic factors on performance. The results indicate that GDP growth has a strong positive impact on deal level returns while credit spreads have a negative association with performance. The impact of GDP growth is larger on high performing investments than on low performers while the magnitude of the negative relationship between returns and credit spreads is larger for higher performing investments. Notably, the results indicate that capital flows have a significant positive impact on top quantile performers and a nonsignificant influence on low and median performers. Combined with the findings of the third study, this suggests that top performers take advantage of improving liquidity conditions by exiting timeously and therefore realise higher performance. Overall, the results suggest that an allocation to the asset class may contribute positively to an allocator's overall portfolio return. Notably, the presence of deal-by-deal performance persistence indicates that the conventional wisdom of selecting GPs that have previously achieved good performance may be applicable when selecting GPs on the African continent. Furthermore, the finding of holding period persistence demonstrates the importance of the ability to timeously realise exits as a dimension of GP selection. This implies that LPs should pay due consideration to whether the track records of GPs demonstrate persistent abilities in evaluating market conditions and making value enhancing decisions about the timing of exits